School-based health education in Yucatan, Mexico about the Chikungunya virus and mosquito illness prevention - Monica Seungah Choo; R. Alexander Blackwood (MDPI AG, 2017)
The Chikungunya virus (CHIKV) has been rapidly spreading throughout Latin America, utilizing pre-existing vectors to infiltrate the immunologically naïve populations. With the current rise of the Zika Virus, there is an urgent need for more rigorous vector control efforts to prevent further Zika breakout. We designed a schoolbased education module on CHIKV and mosquito prevention and presented it to the local students of ages of 6-18 in a rural town called Sudzal in Yucatan, Mexico. We distributed questionnaires before and after education to test the students' knowledge of CHIKV and mosquito prevention. Chisquared test was performed to determine the efficacy of the presentation in increasing their knowledge. The education presentation has proven to effectively educate the local residents in several critical methods of mosquito prevention, increasing the average test scores by 67% post-education. These include applying repellent, staying hydrated during recuperation, and cleaning indoor water containers to eliminate breeding sites (P<0.001). Furthermore, the questionnaire captured the residents' behavioral patterns regarding CHIKV and mosquito prevention and identified cultural, ecological, and socioeconomic factors hindering effective implementation of vector control.